The Analytical Solutions of the Schrodinger Equation for a Single Electron in the Nikiforov-Uvarov Framework - Yulianto, Yacobus; Su'ud, Zaki (Universitas Negeri Semarang, 2020)
In this study, it is intended to show an alternative method to derive the wave function of a single electron as solutions of the Schrodinger equation. The Nikiforov-Uvarov method was chosen to be utilized since this method can solve the Schrodinger equation with several well-known potentials in the non-relativistic mechanics of quantum. The obtained results of this study have succeed to explain the wave function and the energy eigenvalue for a single electron as lectured in quantum physics textbooks. These results prove that the Nikiforov-Uvarov method provides an alternative procedure to solve the Schrodinger equation.